2009
DOI: 10.1016/j.anbehav.2009.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Mysterious attendance cycles in Cory's shearwater, Calonectris diomedea: an exploration of patterns and hypotheses

Abstract: Cory's shearwater logger periodicity seabird Selvagem Grande social interaction synchrony Several species of seabirds show cyclic patterns of attendance at their nesting colonies. We examined the patterns of variation in the numbers of Cory's shearwater at three colonies (two oceanic and one located on the continental shelf), including the world's largest, at Selvagem Grande, Madeira, Portugal and considered several hypotheses concerning their causal mechanisms. At Selvagem Grande, cycles were exceptionally ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…Additionally, the number of birds in the colony is likely to be highest during incubation before breeding birds fail and leave, and before prospecting males, which are highly vocal, leave the colony (James 1985). Secondly, the relationships between acoustic activity and environmental variables in our study are consistent with those reported previously (Granadeiro et al 2009, Buxton & Jones 2012, Borker et al 2014). An example of this is the significantly reduced acoustic activity on moonlit nights, a wellknown phenomenon thought to be a predator avoidance mechanism (Bretagnolle et al 2000, Oppel et al 2014.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the number of birds in the colony is likely to be highest during incubation before breeding birds fail and leave, and before prospecting males, which are highly vocal, leave the colony (James 1985). Secondly, the relationships between acoustic activity and environmental variables in our study are consistent with those reported previously (Granadeiro et al 2009, Buxton & Jones 2012, Borker et al 2014). An example of this is the significantly reduced acoustic activity on moonlit nights, a wellknown phenomenon thought to be a predator avoidance mechanism (Bretagnolle et al 2000, Oppel et al 2014.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, the relationships between acoustic activity and environmental variables in our study are consistent with those reported previously (Granadeiro et al . , Buxton & Jones , Borker et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the remarkable sexual size dimorphism of the species (Thibault et al ., ; see Supporting Information Appendix S1), one would expect a greater sensitivity of male chicks to adverse conditions (Genovart et al ., ). However, and despite parental food delivery being less frequent on full‐moon nights (Klomp & Furness, ; Riou & Hamer, ; but see also Granadeiro et al ., , ; Mougin et al ., ), we did not detect differences in body condition between sexes in two fallouts differing in moon phases (Fig. ).…”
Section: Discussionmentioning
confidence: 99%
“…Our first specific goal was to assess body condition of fledglings attracted to lights throughout the fledging period, taking into account gender, year, bird status (successfully released/dead) and/or plumage characteristics (abundance of down). Parental food delivery and feeding frequency decrease sharply at the end of chick‐rearing period in petrels (Warham, ), and on full‐moon nights (Klomp & Furness, ; Riou & Hamer, ; but see also Granadeiro, Burns & Furness, ; Granadeiro et al ., ; Mougin, Jouanin & Roux, ). The majority of petrel species are sexually size dimorphic, males being larger and heavier than females and, consequently, more sensitive to adverse conditions (Cockburn, Legge & Double, ; Kalmbach & Benito, ).…”
Section: Introductionmentioning
confidence: 98%
“…Vocal activity of burrow-nesting seabirds at colonies is dependent on many environmental factors and thus varies considerably within nights and over the breeding season Granadeiro et al 2009). Instantaneous vocal activity is therefore unlikely to accurately predict nest density, which has affected acoustic population assessments made by human observers in the past (Bolton et al 2010).…”
Section: Acoustic Data Processing and Calibrationmentioning
confidence: 99%